Efektivitas Sistem Informasi Desa terhadap Akurasi Data Kependudukan: Studi Kuantitatif di Kecamatan Pringgarata, Kabupaten Lombok Tengah - Zainuddin, Lalu Ahmad; Nurul Hidayati, Baiq (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to examine the effectiveness of the Village Information System on the accuracy of population data in Pringgarata District, Central Lombok Regency. Accurate population data are essential for development planning and public service delivery at the village level. This research employs a quantitative approach with an explanatory design. Data were collected through structured questionnaires distributed to village officials directly involved in population data management. Data analysis was conducted using descriptive statistics and simple linear regression. The results indicate that the effectiveness of the Village Information System has a positive and significant effect on population data accuracy. A system that is easy to use, reliable, and efficient in data processing reduces input errors and improves data consistency and timeliness. These findings confirm the importance of village-level digital systems in enhancing the quality of population data. Nevertheless, maximizing system benefits requires adequate human resource capacity and effective village administrative governance.